2018
DOI: 10.3390/ma11050774
|View full text |Cite
|
Sign up to set email alerts
|

Investigative Method for Fatigue Crack Propagation Based on a Small Time Scale

Abstract: In-situ scanning electron microscopy (SEM) testing based on a small time scale is proposed to integrally investigate the fatigue crack growth behavior and mechanisms, which is different from the widely-used, cycle-based approach due to its small time scale and comprehensive analysis of the effects of microstructure, crack closure and applied loading on crack growth. In the proposed methodology, the behavior of fatigue crack growth at any time within a loading cycle is observed by SEM to investigate the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…• Small time scale method • DIC • Effect of boundaries and texture on fatigue crack growth behavior [58][59][60][61] • Overloading in fatigue testing…”
Section: Ni-based Single-crystal Superalloysmentioning
confidence: 99%
See 2 more Smart Citations
“…• Small time scale method • DIC • Effect of boundaries and texture on fatigue crack growth behavior [58][59][60][61] • Overloading in fatigue testing…”
Section: Ni-based Single-crystal Superalloysmentioning
confidence: 99%
“…51,[65][66][67] Both hydrogen charging and corrosion fields cause an increase in the fatigue crack growth rate of the material, but due to the limitation of conventional SEM imaging conditions, such experiments need to be conducted under ESEM, and the related work has not been carried out sufficiently. Moreover, in situ SEM fatigue technology has been developed for a variety of applied load variations, such as stress ratio, 80 creep-fatigue, 95 fretting fatigue 38,41 and small time scale methods, 59,60 which make it uniquely suited for exploring the fatigue failure behavior of materials under different loading scenarios. Among these, the small time scale method is an excellent way to investigate the fatigue crack closure behavior of materials, which will be mentioned in Section 4.…”
Section: Section Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are two prevalent views on the effect of precipitate particles on the fatigue properties of aluminum alloy plates [ 8 ]. A few reports have suggested that small GP zones, which are completely coherent with the matrix, contribute to improving the fatigue performance of aluminum alloy plates.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive experiments under both constant and variable amplitudes have been implemented to validate the accuracy of the novel small-timescale model for FCG analysis [30][31][32][33][34]. Previous investigations have indicated that the presented model greatly promotes the fatigue prognosis for structural systems.…”
Section: Introductionmentioning
confidence: 99%